Analisis Partisipasi dan Perilaku Pemilih Menjelang Pemilihan Kepala Desa Serentak - Jopang Liwaul; Muhammad Yunus (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2018)
The election of the Village Head is a manifestation of village democracy in order to determine quality village leadership. This study aims to determine voter participation and behavior ahead of the voting at the village head elections simultaneously in the Puosu Jaya Village Konda District, South Konawe Regency. This research applies quantitative methods through surveys. Samples were chosen randomly by simple random sampling technique. Data collection was done face to face using a structured questionnaire. The results of this study, at the time of the survey a day before the implementation of the Village Head Election, voter participation reached 73.09% of the total recorded in the Final Voters List. The high voter participation was influenced by the promise of money/prizes/goods from prospective/village head candidates with a percentage 44.73% and own initiatives to determine leaders in the village 36.73%. People's behavior in choosing was dominated by money/gift/goods offer as much as 40.37% and their percentage selects candidates who give money/prizes/goods as much as 44%. People consider money politics to be a natural thing (49.82%). The figure of the village head who was expected is one who has financial capacity, a spirit of leadership that is populist and can be emulated.